ANALISIS YURIDIS PENERBITAN SURAT IZIN POLIGAMI KEPADA SESAMA APARATUR SIPIL NEGARA: Juridical Analysis Of The Issuance Of Polygamy Permission Letters To Fellow State Civil Servants - Fadya Ayu Lestari; Pamungkas, Yogo (Faculty of Law, Universitas Trisakti, 2025)
Polygamy, according to the Indonesian Dictionary, is understood as a form of marriage in which one partner has more than one partner simultaneously. The requirements and provisions regarding permission to have more than one wife for state civil servants are strictly regulated in Government Regulation Number 45 of 1990 concerning marriage and divorce permits for civil servants. This research examines the legality of the issuance of polygamy licences by the Regent of South Bolaang Mongondow to fellow State Civil Servants. The focus of the research is directed at the suitability of the issuance of the permit letter with Government Regulation Number 45 of 1990 concerning Marriage and Divorce Permits for Civil Servants, which expressly prohibits female Civil Servants from becoming a second, third, or fourth wife. This research uses a normative juridical method with a descriptive-analytical approach. The result and conclusion shows that the regent's action exceeds legal authority (ultra vires) and violates the principle of legality and the substance of civil service law. It can be concluded that the issuance of the permit causes administrative sanctions and can be cancelled through a lawsuit at the State Administrative Court because it is substantively legally flawed.